Faith, Nation, and Digital Piety: The Moral Politics of Kyai Responses to the 212 Action in Banten - Suryani, Ade Jaya; Rohman, Rohman (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This article explores how Islamic authority, digital communication, and moral politics intersect in post-reform Indonesia through the responses of kyai in Banten to the Aksi Bela Islam (ABI 212) movement. Drawing on fieldwork and interviews with nineteen kyai, it analyses how these clerics interpreted the 2016 blasphemy controversy involving Jakarta’s governor and negotiated their moral positions amid rising Islamic mobilisation. The study identifies three orientations: activist-participatory, spiritual-sympathetic, and critical-pragmatic—each reflecting different moral logics linking faith and civic duty. Digital platforms such as Facebook and WhatsApp became key arenas for coordination and emotional expression, reshaping kyai authority into a form of “networked Islam.” Rather than mirroring conservatism, the kyai’s engagement reveals an ongoing negotiation between piety, nationalism, and democracy, highlighting the reconfiguration of Islamic authority in Indonesia’s digital and moral public sphere.